Interpersonal Communication in Digital Simulations: Dynamics of Self-Disclosure, Trust, and Persuasion - Andi Atrianingsi (ARRUS Journal of Social Sciences and Humanities, 2026)
This study explores the use of digital simulation projects as learning practice spaces to strengthen interpersonal communication competencies in the context of lobbying, presentations, and negotiations. The study used a descriptive qualitative approach with reflexive thematic analysis to understand students' experiences during the implementation of simulation-based Project-Based Learning. Data were obtained through participant observation, documentation of communication performance, and in-depth interviews. The results showed that digital simulations encouraged improved message articulation, argumentation structure, and persuasion strategies in complex communication situations. The collaborative process also facilitated self-disclosure, emotional regulation, and the formation of interpersonal trust. Significant transformations were observed in verbal and nonverbal communication, reflecting the development of students' professional communicative identities. These findings confirm that digital simulations can function as communication laboratories that support reflective and adaptive learning in the digital era.